2014
DOI: 10.1007/s11746-014-2429-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatty Acid Profile of Specialty Maize to Normal Maize

Abstract: Increasing utilization of specialty maize prompted us to evaluate its fatty acid profile. For this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 21 publications
2
33
1
3
Order By: Relevance
“…In five different and recent studies on maize genotypes across the world protein content has been found to vary between 9.4-13%, 11.02-13.02%, 11.02-15.31%, 8.05-11.43% and 6.27-8.06%, while oil content has been found to vary between 3.32-4.70%, 2.56-5.57%, 4.39-9.71%, 3.80-5.02% and 2.7-5.2% respectively (Egesel et al, 2011, Aliu et al, 2012, Sanjeev et al, 2014, Scrob et al, 2014, Chibuike et al, 2015. In India, higher contents of oil (9.71%) and protein (15.31%) have been observed in sweet corn samples and attributed to shriveled grain texture because of an (Sanjeev et al, 2014) which is in consonance with our study. The higher protein content in some of the genotypes especially IC -0617877 (18.7%) and IC-0617880 (17.6%) is quite appreciable and thus may serve as promising donors for this trait in maize breeding programmes.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In five different and recent studies on maize genotypes across the world protein content has been found to vary between 9.4-13%, 11.02-13.02%, 11.02-15.31%, 8.05-11.43% and 6.27-8.06%, while oil content has been found to vary between 3.32-4.70%, 2.56-5.57%, 4.39-9.71%, 3.80-5.02% and 2.7-5.2% respectively (Egesel et al, 2011, Aliu et al, 2012, Sanjeev et al, 2014, Scrob et al, 2014, Chibuike et al, 2015. In India, higher contents of oil (9.71%) and protein (15.31%) have been observed in sweet corn samples and attributed to shriveled grain texture because of an (Sanjeev et al, 2014) which is in consonance with our study. The higher protein content in some of the genotypes especially IC -0617877 (18.7%) and IC-0617880 (17.6%) is quite appreciable and thus may serve as promising donors for this trait in maize breeding programmes.…”
Section: Resultsmentioning
confidence: 96%
“…Fatty acid contents of 9.2-12.7% (palmitic acid), 1.46-2.14% (stearic acid), 23.3-35.4% (oleic acid), 50.8-62.4% (linoleic acid) and 0.42-0.66% (arachidic acid) have been reported in normal maize oil (Egesel et al, 2011). In India, Sanjeev et al (2014) have recorded 12.61-16.22% palmitic acid, 2.63-6.04% stearic acid, 33.54-46.61% oleic acid and 33.00-44.65% linoleic acid contents in the oil obtained from several normal and specialty maize genotypes. Thus, our findings on protein and oil content as well as fatty acid composition in the present study essentially corroborate these reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scientific literature covers many studies comparing maize genotypes for their grain quality, where protein and oil ratios [10], fatty acid compositions [11,12] and mineral matter contents of the genotypes were investigated [13]. However, reports on the comparison of kernel quality traits in high value maize genotypes are rather limited [14]. As a drawback, the "high value" maize genotypes are generally deficient in the other quality traits.…”
Section: Introductionmentioning
confidence: 99%